CYTOTOXIC EFFECT OF THE ETHANOLIC EXTRACT OF LOPHOCEREUS SCHOTTII: A MEXICAN MEDICINAL PLANT. - Orozco-Barocio, Arturo; Paniagua-DomÃnguez, Brenda Lizbeth; BenÃtez-Saldaña, Pedro Alberto; Flores-Torales, Edgardo; Velázquez-Magaña, Salvador; Nava, Julieta Arreola (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Lophocereus schottii is a Mexican cactus known as garambullo whose bark is used for the treatment of cancer, diabetes, ulcers, sores, stomach disorders and tuberculosis. The aim of this study was to evaluate the cytotoxic effect of the ethanolic extract of bark of L. Schottii. To assess these effects we established a flow of experiments in a model of BALB/c mice murine lymphoma. We value first survival of mice inoculated with 2 × 104 L5178Y murine lymphoma cells, orally treated with 10 mg/Kg of the extract for 10 consecutive days; the second assessment was to determine the influence of the immune system, we carry out studies of lymphoproliferation in mice with the same conditions of the previous study, only that the treatment was for 22 days before the completion cell cultures; the third study was to establish the cytotoxic effect of extract of L. schottii using different concentrations, by murine lymphoma cell cultures and splenocytes from healthy mice and finally we assessed the effect in vivo of extract of L. Schottii in a model of solid murine lymphoma inoculating 1 x 107 lymphoma cells in the gastrocnemius muscle observing the development of the tumor. We observed that oral treatment of 10 mg/kg of extract of L. schottii increased survival rate in treated mice; additionally, an intratumoral injection of 50 and 100 mg/kg in a solid murine lymphoma located in the gastrocnemius muscle, allowed a significantly slower tumor evolution. In vitro studies determined that extract inhibited 63% of lymphoma cell growth. With these evidences it is feasible to scientifically validate that ethanolic extract of L. schottii had an effect on L5178Y murine cells lymphoma and could have the same effect in human tumors.